Assessment of factors associated with poor glycemic control among patients with Type 2 diabetes mellitus - Roy, Pratap Kumar; Jha, Sanjay Kumar (Journal of Diabetes and Endocrinology Association of Nepal, 2022)
Background: Diabetes Mellitus type 2 (DM) is a metabolic syndrome with multiple complications. All of those complications are directly related to glycemic control status.. Adequate glycemic control leads to less complications, morbidity and mortality.Aims and objective: The aim of this study is to access the factors associated with poor glycemic control in DM subjects.Materials and methods: This is a OPD based cross-sectional descriptive study conducted in Nobel Medical College and Teaching Hospital among adult DM subjects over the period of one year. A total of 105 cases with DM aged ≥18 years were included and clinical profile, laboratory reports were documented.Results: We found that out of 103 population 60 people (58.2%) had poor glycemic control i.e Hba1c >7% and only 43 (41.8) had good glycemic control i.e. Hba1c